Inclusive education in early childhood settings - Boholano, Helen B.; Navarro, Tizza Marie Menoria-; Jamon, Bernard Evangelicom V.; Cortes, Venus M. (Quezon City : Lorimar Publishing Inc., 2024)
This book is aligned to the current trends in education such as constructivist, integrative, collaborative, inquiry-based, brain-based, research-based and reflective teaching-learning.
Unit 1. Review of the philosophical and legal and bases of inclusion: education for all and the right to education -- Unit 2. Inclusive approach to early education -- Unit 3. Children's disabilities and exceptionalities -- Unit 4. Role of early intervention in inclusive education -- Unit 5. Evolving themes and special concerns -- Unit 6. Early Intervention programs -- Unit 7. Planning for inclusion customizing early intervention -- Unit 8. An Overview of basic instructional principles.
Keywords: EARLY CHILDHOOD EDUCATION; INCLUSIVE EDUCATION